Erosion of gadolinia doped EB-PVD TBCs - Steenbakker, R J L; Wellman, R. G.; Nicholls, John R. (Elsevier Science B.V., Amsterdam., 2006)
Gadolinia additions have been shown to significantly reduce the thermal conductivity of EB-PVD TBCs. The aim of this paper is to further the understanding on the effects of dopants on the erosion resistance of EB-PVD TBCs by studying the effects of 2 mol% Gd2O3 additions on the room and high temperature erosion resistance of as received and aged EB-PVD TBCs. Previously it has been reported that gadolinia additions increased the erosion rate of EB- PVD TBCs, this is indeed the case for room temperature erosion, however under high temperature (825 Ã Â°C) erosion conditions this is not the case and the doped TBCs have a slightly lower erosion rate than the standard YSZ EB-PVD TBCs. This has been attributed to a change in the erosion mechanisms that operate at the different temperatures. This change in mechanism was not expected under the impact conditions used and has been attributed to a change in the column diameter, and how this influences the dynamics of particle impaction
Keywords: Erosion; EB-PVD TBC; Dopant effects